Secure Voting Using Bio-metric Authentication - Gupta, Lalit Kumar; Tiwari, Utkarsh; Chaudhary, Manoj Kumar; Kasaudhan, Kuldeep (International Journal of Computer Sciences and Engineering, 2019)
In this era of technology and advancement, everything is getting online. Today people want to be part of everything but didn't want to spare time for it. So when it comes to voting or polling, giving it time feels a very painful task, so why it should not be online? Online voting system as the name suggests is the concept of getting voting and polling done online, simply termed as ‘Internet Voting'. And to ensure security and authenticity of the vote, biometric authentication is done. This method is smart, quick, reliable, and secure. The earlier voting system was very time consuming and also were not so reliable. In the present day, the commonly used voting machine is EVM (Electronic Voting Machine), which have no mechanisms to verify the voter while casting vote and thus fake votes can be cast. But in the online voting system, Biometric authentication using fingerprint and unique voter identification number (here registration number provided during registration of voter) make it the most secure way of voting. This model covers all the limitation of present time in the voting system and is the most advanced of its time.